Pengaruh Gaya Kepemimpinan, Reward Dan Punishment Terhadap Kinerja Pegawai Pada Dinas Perumahan, Kawasan Permukiman Dan Cipta Karya Kabupaten Malang - Moch. Irvan Rusyadi; Hadi Sunaryo; Mohammad Rizal (UNIVERSITAS ISLAM MALANG, 2021)
AbstractThe purpose of this study was to describe the leadership style, reward, punishment, and employee performance and to determine the effect of leadership style, reward, and punishment on employee performance partially or simultaneously. This research method uses quantitative methods and this type of research is explanatory research. The sample of this research was 47 employees of the Housing, Settlement and Human Settlements Department of Malang Regency.To obtain accurate and detailed data, this study used a data collection method with a questionnaire. Data analysis used was instrument test, normality test, multiple linear regression analysis, classical assumptions, and hypothesis testing using SPSS 20 for Windows. The results of this study indicate that the leadership style, reward, and punishment have a simultaneous effect on employees of the Housing, Settlement Areas, and Cipta Karya Malang Regency employees. Whereas partially, leadership style has no effect on employee performance, reward has an effect on employee performance, and punishment affects employee performance at the Housing, Settlement Areas, and Cipta Karya Malang Regency. Keywords: Leadership Style, Reward, Punishment and Employee Performance